Environmental and Its Implications for Sustainable City: A Lesson From the Experience of Kampong Go Green in Malang - Cahyasari, Erlita (Badan Penerbitan Jurnal (BPJ) FIA-UB, 2021)
Sustainable city development is an attempt to increase societyâ€™s life quality. Environmental awareness is no longer local normativity, but a construct of shared life. A good environmental awareness is not merely a national discourse but has become a global and urgent importance. This paper aims to identify and analyze the implications of environmental governance in sustainable city development. It is a descriptive research with qualitative approach. The result of this study shows that the community and the authorities in kampong Kampong Go Green of Malang are the main factors that determine the success of environmental governanceÂ process in sustainable city development.